PERANCANGAN AUGMENTED REALITY TATA LOKASI GEDUNG DAN RUANGAN PADA KAMPUS I UINSU MEDAN BERBASIS ANDROID - Wiranda Wiranda; Ilka Zufria; Ali Ikhwan (UIN Sumatera Utara Medan, 2021)
Augmented reality is a technologycal development that can display two dimensional or three dimensional virtual objects into a real scope and then display them or display them in real time. Augmented reality technology in the application of building and room location layout on UINSU Medan campus I is an application that uses the markerless user defined target method, which is a method that applies it without using a marker or marker to dismantle the 3D augmented reality map of UINSU Medan campus I environment. This application program can help users to find buildings and rooms within the building, without having to ask the security guard or see an image map that is on campus locations, with this technology users can determine where children are without having to be in first. Campus environment. This application runs on the Android operating system and is offline based, so it can be more easily accessed by all users.